Islamic Perspectives on the New Millennium - Hooker, Virginia Matheson; Saikal, Amin (Institute of Southeast Asian Studies, 2004)
The early years of the twenty-first century have been characterized by a sense of widespread anxiety and fear because of the violent activities of groups of terrorists who claim they act in the name of Islam. Their acts of terrorism, viewed by a majority in the Muslim world as crimes which must be subject to the law, are in tragic contrast to the efforts of many Muslim intellectuals who have been working for the past several decades to find common ground between people of all faiths based on the universality of humankind. This book aims to bring to the attention of non-Muslims, in particular, the range of views which Muslims in the Middle East and in South and Southeast Asia hold on six topics of importance to life in the twenty-first century. The topics have been addressed from the internal Muslim point of view to provide readers with a sense of the main debates within Islam on each of the issues. The topics addressed are: the new world order; globalization and modernity; banking and finance; the nation-state; the position of women; and law and knowledge. The chapters have been written by Muslims and non-Muslims, each of whom is an expert on the area about which they write. The chapters are presented in pairs which offer Middle Eastern (and in one case South Asian) points of view which are matched by Southeast Asian perspectives on each of the six topics. While the media is quick to report on the more violent expressions of Islam, including terrorism, the vigorous debates, which now characterize the intellectual discourse in Muslim communities, are rarely if ever reported. This book not only describes and analyses those debates but also reflects the views of many Muslims across the world, emphasizing the connections and contrasts between the Middle East and Southeast Asia.